Optical determination of the mass density of amorphous and microcrystalline silicon layers with different hydrogen contents - Remeš, Z.; Vaněček, Milan; Torres, Pedro; Kroll, U.; Mahan, A. H.; Crandall, R. S. (My University, 1998)
We have measured the density of amorphous and microcrystalline silicon films using an optical method. The mass density decreases with increasing hydrogen content, consistent with a hydrogenated di-vacancy model that fits the data for amorphous silicon. Material produced by hot wire assisted chemical vapour deposition, with low hydrogen content, has a higher density and is structurally different from glow discharge material with hydrogen content around 10 at.%. The lower density microcrystalline silicon seems to be porous.
Keywords: mass density; silicon layers; hydrogen contents